“I think we're on a cusp of some change:” coping and support for mental wellness among Black American women - McCall, Terika; Foster, Meagan; Tomlin, Holly; Adepoju, Bolatito; Bolton-Johnson, Mckenzie; Bellamy, Chyrell D. (Frontiers in Psychology, 2025)
IntroductionPublic discussions in the media (e.g., social media and reality shows) about Black women's mental health have become more common. Notably, celebrities have become more vocal about their own mental health challenges and sought to normalize seeking care. This study aimed to gain a better understanding of Black women's: (1) past and current causes of stress, anxiety, and depression, and coping skills used; (2) their attitudes and perceptions toward mental health and receiving mental health treatment; and (3) times in their life they felt anxious or depressed, and what type of support or resources would have been helpful to have access to.MethodsFocus groups were conducted with 20 women (mean age 36.6 years, SD 17.8 years), with 5 participants per group. Descriptive qualitative content analysis of the focus group transcripts was conducted.ResultsResults consistently showed that intersectional identities of being both Black and a woman resulted in feelings of both hypervisibility and invisibility, representation matters when it comes to mental health providers, an increased openness to therapy across age groups, and a willingness to try digital health tools (e.g., smartphone app) for mental health needs. There is still work to be done to normalize mental health treatment among Black women.DiscussionSubgroups within the community (e.g., young adults) have less stigma around mental health and are acting as catalysts for change. Intentional inclusion of Black women in mental health research and evolving treatment paradigms is important to eliminate inequities in access to culturally relevant mental health care.